Long Noncoding RNA OR7E156P/miR-143/HIF1A Axis Modulates the Malignant Behaviors of Glioma Cell and Tumor Growth in Mice - Zhao, Haiting; Du, Peng; Peng, Renjun; Peng, Gang; Yuan, Jian; Liu, Dingyang; Liu, Yi; Mo, Xin; Liao, Yiwei (Frontiers in Oncology, 2021)
Gliomas are characterized by high incidence, recurrence and mortality all of which are significant challenges to efficacious clinical treatment. The hypoxic microenvironment in the inner core and intermediate layer of the tumor mass of gliomas is a critical contributor to glioma pathogenesis. In this study, we identified an upregulated lncRNA, OR7E156P, in glioma was identified. The silencing of OR7E156P inhibited cell invasion and DNA synthesis in vitro and tumor growth in vivo. OR7E156P was intricately linked to the HIF1A pathway. Hypoxia could induce OR7E156P expression, whereas OR7E156P silencing decreased HIF1A protein levels under hypoxic conditions. Hypoxia promoted glioma cell invasion and DNA synthesis, and HUVEC tube formation, whereas OR7E156P silencing partially reversed the cellular effects of hypoxia. HIF1A overexpression promoted, whereas OR7E156P silencing inhibited tumor growth; the inhibitory effects of OR7E156P silencing on tumor growth were partially reversed by HIF1A overexpression. miR-143 directly targeted OR7E156P and HIF1A, respectively. miR-143 inhibition increased HIF1A protein levels, promoted glioma cell invasion and DNA synthesis. Moreover, they enhanced HUVEC tube formation, whereas OR7E156P silencing partially reversed the cellular effects of miR-143 inhibition. HIF1A targeted the promoter region of miR-143 and inhibited miR-143 expression. Altogether a regulatory axis consisting of OR7E156P, miR-143, and HIF1A, was identified which is deregulated in glioma, and the process of the OR7E156P/miR-134/HIF1A axis modulating glioma cell invasion through ZEB1 and HUVEC tube formation through VEGF was demonstrated.